Design for occupational safety and health: key attributes for organisational capability. Issue 11 (18th November 2019) - Manu, Patrick; Poghosyan, Anush; Mahamadu, Abdul-Majeed; Mahdjoubi, Lamine; Gibb, Alistair; Behm, Michael; Akinade, Olugbenga O.
Abstract : Purpose: Against the backdrop of the contribution of design to the occurrence of occupational injuries and illnesses in construction, design for occupational safety and health (DfOSH) is increasingly becoming prominent in the construction sector. To ensure that design interventions are safe for construction workers to build and maintain, design firms need to have the appropriate organisational capability in respect of DfOSH. However, empirical insight regarding the attributes that constitute DfOSH organisational capability is lacking. The purpose of this paper, which trailblases the subject of DfOSH organisational capability in construction, is to address two key questions: what organisational attributes determine DfOSH capability? What is the relative priority of the capability attributes? Design/methodology/approach: The study employed three iterations of expert focus group discussion and a subsequent three-round Delphi technique accompanied by the application of voting analytic hierarchy process. Findings: The study revealed 18 capability attributes nested within six categories, namely: competence (the competence of organisation's design staff); strategy (the consideration of DfOSH in organisation's vision as well as the top management commitment); corporate experience (organisation's experience in implementing DfOSH on projects); systems (systems, processes and procedures required for implementing DfOSH); infrastructure (physical, and information and communication technology resources); and collaboration (inter- and intra-organisational collaboration to implement DfOSH on projects). Whilst these categories and their nested attributes carry varying weights of importance, collectively, the competence-related attributes are the most important, followed by strategy. Originality/value: The findings should enable design firms and other key industry stakeholders (such as the clients who appoint them) to understand designers' DfOSH capability better. Additionally, design firms should be able to prioritise efforts/investment to enhance their DfOSH capability.